Role of protease maturation lipoprotein in osmoadaptation of Streptococcus mutans. Issue 1 (26th June 2014) - Kunii, Maiko; Arimoto, Takafumi; Hasegawa, Tokuji; Kuwata, Hirotaka; Igarashi, Takeshi
Abstract Osmoadaptation may be an important trait for the pathogenicity of Streptococcus mutans. However, how this organism adapts to changes in osmolality in the oral cavity remains unclear. In this study, we showed that S. mutans utilizes K+ for osmoadaptation, in which protease maturation lipoprotein (PrtM) plays an important role. Although growth of the wild‐type strain was impaired in a hyperosmotic medium [brain heart infusion (BHI) containing 0.3 M NaCl] compared with that in an unmodified BHI, the prtM mutant grew much more poorly in 0.3 M NaCl BHI. Comparison of growth behavior in the hyperosmotic medium supplemented with different osmoprotectants revealed that only the addition of K+ allowed the bacteria to overcome the impairment of growth caused by the high osmolality. These results suggest that K+ is an important compatible solute for S. mutans. Moreover, K+‐associated recovery of growth was not observed for the prtM mutant, indicating that PrtM plays a critical role in the utilization of K+. Quantitative reverse‐transcriptase polymerase chain reaction analysis showed that prtM was induced by osmotic stress, implying that prtM is an osmoresponsive gene. These findings suggest that K+ is an important compatible solute for S. mutans, and that the osmoresponsive lipoprotein PrtM is involved in K+ utilization, contributing to osmoadaptation of S. mutans.